Wireless Monitoring of Household Electrical Power Meter Using Embedded RFID with Wireless Sensor Network Platform. (18th June 2014) - Boonsong, Wasana; Ismail, Widad
Tracking and monitoring system using radio frequency identification (RFID) have gained a lot of improvements especially for applications that need automation with reduction in human intervention and become more interesting nowadays with the increasing market demand for internet of things (IoT) technologies. The objective of this study is to improve the machine-to-machine (M2M) communication using active RFID with wireless sensor networks (WSNs) with heterogeneous data transfer (regardless of power meter type) for monitoring and identification of household electrical consumption. M2M is a popular technology and has become a part of our daily life. WSN through ZigBee technology is applied to monitor data and to read the load consumption from the electrical household power meter by embedding a tag module into the meter. In-house built-in tag was embedded into an electrical power meter with a power management circuit communicating to a reader at an RF signal of 2.45 GHz based on the star network topology with the sleep mode function. The experimental results indicated that the electrical power meters with embedded tags successfully worked wirelessly with acceptable mean value of electrical consumption difference in Watts more than those without tags (standalone meter), which is in the range of 2.44 W to 2.5 W based on 10-hour measurements.